Limited Equity Cooperatives: The Non-Economic Value of Homeownership - Julie D. Lawton (Washington University Journal of Law & Policy, 2014)
Economists have argued there are two main purposes of homeownership. The first is housing as a utility for consumption, and the second is housing as an investment vehicle. Legal scholars, on the other hand, view homeownership in more personal terms. Margaret Radin, in her watershed article, argues that homeownership is so closely imbued with the person that it is affirmatively part of one‘s self—the personhood of property. Radin suggests that one‘s home is such a part of the way a person constitutes oneself that the property becomes an element of personhood, something no longer entirely external to the person. In response, however, Stephanie Stern argues there is little to no empirical evidence to support this proposition. She argues instead that homeownership has been provided unwarranted legal and economic protection, and has no more intrinsic value to the individual than any other possession. Many Americans embrace homeownership for reasons beyond investment. This Article evaluates the meaning of homeownership, particularly when wealth creation is not the primary goal. There are non-economic values to homeownership, particularly for low- and moderate-income residents, which remain unexplored. This Article seeks to evaluate the arguments of legal scholars and economists in light of the limited equity cooperative, a form of homeownership that significantly limits equity appreciation for the owner. While the limited equity cooperative is an older form of homeownership, it has reemerged as a valued homeownership option, especially, though not exclusively, for low- and moderate-income residents. This Article works to dispel the argument that homeownership, particularly limited equity cooperative homeownership, is less valuable for a homeowner because equity appreciation is restricted or because limited equity cooperatives are a non-traditional form of homeownership. Part I of the Article will provide a brief history of the federal government‘s efforts to promote homeownership, particularly for low- and moderate-income individuals. Part II will provide a brief description of the different types of traditional homeownership models common in the United States. Part III will provide a history of and evaluate one of the alternatives to the traditional homeownership model—the housing cooperative, specifically, the limited equity cooperative. Part IV concludes with an analysis of the non-economic value of homeownership as it relates to limited equity cooperative homeownership.
Keywords: homeownership; real property; housing